Factors hindering and boosting SDG7 implementation in EU countries - Kuc-Czarnecka, Marta; Markowicz, Iwona; Sompolska-Rzechuła, Agnieszka; Stundžienė, Alina (Technological and Economic Development of Economy, 2025)
One of the sustainable development goals (SDG7) is to ensure access to clean and affordable energy, which is related to most other SDGs and plays a crucial role in economic development and human well-being. The aim of the article is to identify factors that enhance and delay one of the most crucial goals of sustainable development, SDG7. The study’s originality lies in the spatiotemporal approach to analysing the impact of selected factors on the development of green energy and increasing its availability. Three groups of potential SDG7 determining factors have been identified: ecological, social and economic. The proposed approach and the use of sensitivity analysis to variables weighting and ranking constructions of EU countries is an innovative aspect of the work and fills the gap in research on SDG7. The study showed that Denmark and Sweden occupy leading positions in the rankings based on the extent of SDG7 implementation. In contrast, Bulgaria, Cyprus and Lithuania occupied one of the last positions. The results of panel-data model estimations showed that in each estimated model, the same “indispensable variables” significantly affect the implementation of SDG7. Among these variables, only the unemployment rate significantly negatively impacted the SDG7 execution. First published online 15 November 2024